Advances in Neuroprotection in Glaucoma: Pharmacological Strategies and Emerging Technologies - Li-Hsin Wang; Chun-Hao Huang; I-Chan Lin (MDPI AG, 2024)
Glaucoma is a major global health concern and the leading cause of irreversible blindness worldwide, characterized by the progressive degeneration of retinal ganglion cells (RGCs) and their axons. This review focuses on the need for neuroprotective strategies in glaucoma management, addressing the limitations of current treatments that primarily target intraocular pressure (IOP) reduction. Despite effective IOP management, many patients continue to experience RGC degeneration, leading to irreversible blindness. This review provides an overview of both pharmacological interventions and emerging technologies aimed at directly protecting RGCs and the optic nerve, independent of IOP reduction. Pharmacological agents such as brimonidine, neurotrophic factors, memantine, Ginkgo biloba extract, citicoline, nicotinamide, insulin, and resveratrol show promise in preclinical and early clinical studies for their neuroprotective properties. Emerging technologies, including stem cell therapy, gene therapy, mitochondrial-targeted therapies, and nanotechnologies, offer innovative approaches for neuroprotection and regeneration of damaged RGCs. While these interventions hold significant potential, further research and clinical trials are necessary to confirm their efficacy and establish their role in clinical practice. This review highlights the multifaceted nature of neuroprotection in glaucoma, aiming to guide future research and clinical practice toward more effective management of glaucoma-induced neurodegeneration.